PERAN STRATEGI KOMUNIKASI PEMASARAN BUSINESS TO BUSINESS (B2B) DALAM MENINGKATKAN PENJUALAN ONLINE (STUDI KASUS PADA BISNIS FIRSTHAND SELLER) - Faradiba Sabina Erdian; Iwan Sukoco Sukoco; Nurillah Jamil Achmawati Novel; Cecep Safa’atul Barkah (JURNAL LENTERA BISNIS, 2023)
The use of the internet and social media has brought significant changes to buying and selling activities, especially in online shopping. In the Business to Business (B2B) context, marketing communication strategies play a crucial role in enhancing online sales. This research aims to analyze the role of marketing communication strategies in increasing online sales for small B2B businesses, such as Mimosh. The research employs a qualitative descriptive approach, using observation and interviews with Mimosh's owner and CEO. The research findings indicate that Mimosh utilizes social media platforms, such as Facebook and WhatsApp groups, for online marketing. The applied marketing communication strategies include personal selling and relationship marketing. Personal selling is carried out through video, photo, and written content on Facebook to reach potential audiences and resellers. Mimosh also builds a professional profile with comprehensive information about products, advantages, benefits, and clear contact details. Relationship marketing is achieved by providing client satisfaction and building long-term relationships. This research highlights the importance of appropriate communication strategies in the B2B business context and provides recommendations to Mimosh management based on the research findings. Keywords: Business B2B, Online Sales, Marketing Communication Strategy